A Glimpse into the Medical Practice among Jews around 1500 : Latin-German Pharmaceutical Glossaries in Hebrew Characters extant in Ms Leiden Universiteitsbibliotheek, Cod. Or. 4732/1 (SCAL 15), fols. 1a-17b - Fischer, Klaus-Dietrich,; Bos, Gerrit, (Religious Studies, Theology and Philosophy E-Books Online, Collection 2021, ISBN: 9789004441309., 2021)
With A Glimpse into Medical Practice among Jews around 1500: Latin-German Pharmaceutical Glossaries in Hebrew Characters extant in Ms Leiden, Universiteitsbibliotheek, Cod. Or. 4732/1 (SCAL 15), fols. 1a-17b , Gerrit Bos and Klaus-Dietrich Fischer present an edition of two unique medieval lists of medico-botanical terms in Latin and German, written in Hebrew characters. Jewish physicians probably used these kinds of lists for the acquisition of pharmaceuticals they needed for the preparation of medicines. The edition with a total of 568 entries features transcriptions from the Hebrew, tables and indexes of the analysed terms in a regularized form, and a facsimile of the Leiden manuscript. Many of the German plant names featuing in the edition are not listed in the otherwise monumental reference work Wörterbuch der deutschen Pflanzennamen ( Dictionary of German Plant Names ) by the German botanist Heinrich Marzell. This testifies to the value of these glossaries for further research. It is also useful to see which Latin forms were in current use at the time of creation of the edition.